Removal of duloxetine from aqueous solution by adsorption onto chemical crosslinked alginate beads - Ertugruloglu, Pinar; Gulcan, Hayrettin Ozan; Ifebajo, Ayodeji Olugbenga; Fallah, Amirhossein; Sahin, Mustafa Fethi; Gazi, Mustafa (Taylor & Francis Inc, 2022)
There is raising concern on the impact of pharmaceutical active compounds (PACs) on nature, since their detection in surface water, wastewater effluents, and even drinking water can reach to life-threatening levels in near future. Among them, antidepressants-related contamination is of particular significance with respect to their worldwide and uncontrolled employment. From this point of view, it is important to develop technologies to treat water sources for decontamination purposes. Within this study, we have explored the potential of glutaraldehyde crosslinked alginate beads to effectively adsorb a commonly used antidepressant drug, duloxetine hydrochloride (DLU), from aqueous solution. Batch adsorption studies were carried under various experimental conditions (i.e., adsorbent dosage, initial DLU concentration, and contact time) to identify the optimum interaction characteristics between the alginate beads and DLU. The experimental results showed that the adsorption capacity of the alginate beads increased with increase in DLU initial concentration and the equilibrium data fitted satisfactorily with the Freundlich model (R-2 > 0.99). The maximum adsorption capacity at 298 K was 14.83 mg of DLU per gram of the crosslinked alginate bead at pH 7.4, while the kinetic data were best expressed through pseudo-second-order kinetic model. Results obtained clearly indicate that the glutaraldehyde crosslinked alginate beads displayed a high affinity to bind DLU and can be employed as an adsorbent for removal of DLU from aqueous solution.
Keywords: Antidepressant drugs; crosslinked alginate; drug adsorption; drug removal; duloxetine